2020
DOI: 10.20960/nh.02942
|View full text |Cite
|
Sign up to set email alerts
|

Body composition assessment before and after weight loss following a Roux-en-Y gastric bypass. Are bioimpedanciometry estimations reliable?

Abstract: Objetivo: el objetivo de este estudio fue evaluar la prevalencia de hipovitaminosis D en los candidatos a cirugía bariátrica (CB) y su relación con factores de riesgo y los componentes del síndrome metabólico. Material y métodos: los parámetros clínicos, antropométricos y bioquímicos se midieron en 56 pacientes caucásicos incluidos en un protocolo de cirugía bariátrica entre enero y junio de 2014. Los pacientes fueron estratificados en tres grupos de acuerdo al status de vitamina D: suficiencia (≥ 40 ng/ml), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Recent research has shown the predictive nature of cachexia, leading to sarcopenia and frailty, for postoperative recurrence in cancer patients. [2][3][4] Since sarcopenic patients, evaluated by muscle mass, have poorer tolerance to cancer therapies with a greater incidence of complications, chemotherapy toxicity, and perioperative problems, including recurrence, the evaluation of sarcopenic status can help to develop treatment strategies. In addition, accumulating evidence has shown that sarcopenia and frailty can be induced by various mechanisms, such as malnutrition, systemic inflammation, and other organ diseases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent research has shown the predictive nature of cachexia, leading to sarcopenia and frailty, for postoperative recurrence in cancer patients. [2][3][4] Since sarcopenic patients, evaluated by muscle mass, have poorer tolerance to cancer therapies with a greater incidence of complications, chemotherapy toxicity, and perioperative problems, including recurrence, the evaluation of sarcopenic status can help to develop treatment strategies. In addition, accumulating evidence has shown that sarcopenia and frailty can be induced by various mechanisms, such as malnutrition, systemic inflammation, and other organ diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study, to our knowledge, demonstrating the effectiveness of ECW/TBW as a predictive factor for recurrence in cancer patients. Recent research has shown the predictive nature of cachexia, leading to sarcopenia and frailty, for postoperative recurrence in cancer patients 2–4 . Since sarcopenic patients, evaluated by muscle mass, have poorer tolerance to cancer therapies with a greater incidence of complications, chemotherapy toxicity, and perioperative problems, including recurrence, the evaluation of sarcopenic status can help to develop treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the present study suggested that the important parameters in BIA would not be SMI or FFMI, which are secondarily calculated based on electric current, resistance, and reactance, but rather ECW/TBW, which is directly calculated. Several reports (20,21) have also indicated that FFM measured by BIA would not be appropriate parameters for detecting the frail population among cancer patients, which might be related to the effect of body fluid retention on muscle mass estimation via altered impedance. Furthermore, this study indicated that ECW/TBW would more accurately detect the frail population among LC patients with potentially poor PS and/or ageing than Ph-A, directly calculated based on electric current, resistance, and reactance.…”
Section: Discussionmentioning
confidence: 99%